1979
DOI: 10.1084/jem.150.6.1448
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte transformation induced by autologous cells. VIII. Impaired autologous mixed lymphocyte reactivity in patients with acute infectious mononucleosis.

Abstract: The autologous mixed lymphocyte reaction (MLR) is severely impaired in patients with acute infectious mononucleosis. Reactivity returned during the course of convalescence. The allogeneic MLR was not impaired in these patients. B cells from patients with infectious mononucleosis do not stimulate autologous T-cell proliferation, and this observation appears to explain the cellular basis of the impaired autologous MLR in infection. Two explanations for the B-cell defect were considered: (a) the influence of seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
1

Year Published

1980
1980
1992
1992

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 20 publications
2
18
1
1
Order By: Relevance
“…The AMLR is decreased in SLE (8, 9), chronic lymphocytic leukemia (19) and infectious mononucleosis (19). The analogous interaction between syngeneic spleen T and non-T cells is markedly diminished in New Zealand black mice (20), an experimental model DISCUSSION The AMLR is a phenomenon by which T cells proliferate in response to non-T cell surface antigens (7,8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AMLR is decreased in SLE (8, 9), chronic lymphocytic leukemia (19) and infectious mononucleosis (19). The analogous interaction between syngeneic spleen T and non-T cells is markedly diminished in New Zealand black mice (20), an experimental model DISCUSSION The AMLR is a phenomenon by which T cells proliferate in response to non-T cell surface antigens (7,8).…”
Section: Resultsmentioning
confidence: 99%
“…However, Kuntz et al (9) concluded that a B cell defect alone might cause the reduced response in SLE. In chronic lymphocytic leukemia and infectious mononucleosis, this defect mainly exists in B cells (18,19). There is considerable evidence that the responding cells in AMLR are T cells (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, deficient AMLR in KS could be associated with decreased NK that might play a role in the increased susceptibility to viral infection and development of KS in homosexuals. The role of AMLR in immune surveillance and resistance to viruses is further supported by its deficiency in Hodgkin's disease (24,25), colon carcinoma (25), and infectious mononucleosis (26).…”
Section: Methodsmentioning
confidence: 99%
“…The impaired blood AMLR of cancer patients seems to be derived from the disease itself because the patients had no previous history of anticancer chemotherapy or radiation therapy at the time of the study and were <50 yr old. Similarly, pronounced depression of AMLR has been reported in the peripheral blood of patients with systemic lupus erythematosus (20,21), chronic lymphocytic leukemia (22), Hodgkin's disease (23), infectious mononucleosis (28), and Sj6gren's syndrome (24). (21), and the impaired AMLR in patients with Hodgkin's disease is due to the responder T cell population in two cases (23).…”
Section: Resultsmentioning
confidence: 99%